Experimental Investigation on Hard Rock Breaking with Fiber Laser: Surface Failure Characteristics and Perforating Mechanism - Xiaofeng Yang; Xin Zhou; Hongliang Zhu; Jiaheng Zhou; Yanhong Li (Advances in Civil Engineering)
The rock-breaking characteristics and the influence factors of laser perforation are investigated in this study. A series of fiber laser perforation experiments on basalt, sandstone, and granite were conducted. Experimental measurements of rock failure morphologies and composition tests showed that the main surface features are thermal cracks and glazed layer formed by the melting and condensing of rock in laser perforation. It is also found that higher quartz content could help reduce the glazed degree of rock. Comprehensive results showed that the laser rock perforation is mainly formed by thermal fractures, the decline of molten pool, and the evaporating and splashing of the special melted rock components. The depth of rock perforation and SE usually increase with the laser irradiation time, while the ROP gradually decreases. With the increase of laser power, the perforation depth and ROP gradually increase, while the SE initially decreases and then increases indicating that there is an optimal power that maximizes perforation efficiency. It is believed that the strength of rock is the main factor affecting laser perforation efficiency, and the lower rock strength resulted in deeper perforation depth, higher ROP, and lower SE.